Outcomes Assessment of the Regional Health Information Exchange - Mäenpää, T.; Asikainen, P.; Gissler, M.; Siponen, K.; Maass, M.; Saranto, K.; Suominen, T. (Methods of Information in Medicine, 2011)
Background: The implementation of a technology such as health information exchange (HIE) through a Regional Health Information System (RHIS) may improve the mobilization of health care information electronically across organizations. There is a need to coordinate care and bring together regional and local stakeholders.Objectives: To describe how HIE had influenced health care delivery in one hospital district area in Finland.Method: Trend analysis was used to evaluate the influence of a regional HIE. We conducted a retrospective, longitudinal study for the period 2004–2008 for the eleven federations of municipalities in the study area. We reviewed statistical health data from the time of implementation of an RHIS. The t-test was used to determine statistical significance. The selected outcomes were the data obtained from the regional database on total appointments, emergency department visits, laboratory tests and radiology examinations, and selected laboratory tests and radiology examinations carried out in both primary care and special health care.Results: Access to HIE may have influenced health care delivery in the study area. There are indications that there is a connection between access to regional HIE and the number of laboratory tests and radiology examinations performed in both primary care and specialized health care, as observed in the decreased frequency in outcomes such as radiology examinations, number of appointments, and emergency department visits in the study environment. The decreased frequencies of the latter suggest an increased efficiency of outpatient care, but we were not able to estimate to what extent the readily available comprehensive clinical information contributed to these trends.Conclusion: Outcome assessment of HIE through an RHIS is essential for the success of health information technology (HIT) and as evidence to use in the decision-making process. As health care information becomes more digital, it increases the potential for a strong HIE effect on health care delivery.
Keywords: Regional health information system (RHIS); regional health information exchange; health outcome; assessment